Literary canon studies: methodological guidelines - Šeina, Viktorija (Literatūra, 2019)
The article presents for the Lithuanian audience an interdisciplinary approach of literary canon studies that integrates diverse methods of various disciplines (sociology of literature and culture, literary and cultural history, teaching of literature, text reception and aesthetic response history, memory and media research and bibliography studies). The most intense development of literary canon studies can be observed in Western Europe and the United States in the last decade of the 20th century. This was due to the fact that the scholars engaged in the field of postcolonialism, gender studies and neo-Marxism gave it a strong impulse by initiating a debate about insufficient representation of some social groups (women, racial or ethnic minorities and people from lower social strata) in high school curricula in the USA. The debate was expanded into theoretical polemics of whether the canon is formed by means of objective aesthetic criteria or, on the contrary, canon depends on the social contract. Methodologically, investigations of literary canon that are genetically related to the tradition of sociology of culture seem to be the most productive, while this perspective provides an apparatus for a detailed investigation of relations between specific interests of literary field and wider national, social or group interests.The framework of this article is based on the studies of John Guillory, Renate von Heydebrand and Simone Winko. Their essential starting point is the understanding of the canon as a sociocultural process in which the political elite selects a corpus of significant texts in accordance with tradition and formulates practices that ensure the transmission of those texts for future generations. Therefore, canon formation turns to be a strategy based on complex relations of evaluation, cognition and actions that aims to conserve this selected knowledge and transmit it to future generations. The structure of the canon is directly related to the notion of literature and literariness; a society (or its group) defines its canon by considering what they recognize as valuable.Unlike religious canons, which can only be constructed by theologians, there are a lot of canonizing institutions (schools, universities, literary criticism, theatre repertoire, book market, libraries, etc.) involved in the formation of literary canons. They do not create any well-balanced system of the canon but rather conduct diverse practices of canonization. We can distinguish a micro and macro level in the process of canon formation. The micro level contains a lot of separate actions of canonization that propel the canonization process which enables the canon formation at macro level. Origin, stabilization and transformation of literary canon are multidimensional processes, thus it is essential not to lose sight of the interaction of separate dimensions.
Keywords: literary canon; canon wars; socialization of canon; John Guillory; Renate von Heydebrand